Translation Methods and Quality of the English Translation of Putri Mambang Linau Folklore - Arif Hariadi (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Abstract This study examines the translation methods employed in the English version of the Putri Mambang  Linau folklore and describes their associated translation quality profiles. The study adopts a descriptive qualitative approach by applying Peter Newmark’s translation method framework and Nababan’s Translation Quality Assessment (TQA) model. The data comprise 230 sentences, consisting of 115 source-language sentences and 115 corresponding target-language sentences from one bilingual edition of the folklore. The findings indicate that the translation achieves a fairly good level of quality, with an overall mean TQA score of 2.43. Communicative and semantic translation methods are the most frequently identified methods. Descriptively, different translation methods are associated with different quality patterns within the analyzed text, particularly in relation to the balance between semantic preservation, cultural representation, acceptability, and readability. Semantic-oriented choices tend to retain source-text meaning and culture-specific elements more closely in particular contexts, whereas communicative-oriented choices tend to support naturalness and accessibility in the target text. These patterns should not be interpreted as evidence of statistical significance or causal effects, given that the analysis is based on a single bilingual text translated by one translator and uses descriptive comparison. The study contributes to translation research by demonstrating how translation methods can be examined alongside translation quality and cultural representation within a specific Indonesian folklore translation. Its novelty lies in identifying the textual pattern and potential trade-off between semantic preservation and target-reader-oriented naturalness in this particular bilingual edition.